Chemical and sensory characterisation of Sangiovese red wines: Comparison between biodynamic and organic management. (15th January 2015) - Parpinello, Giuseppina Paola; Rombolà, Adamo Domenico; Simoni, Marco; Versari, Andrea
Highlights: Study of the effect of biodynamic preparation on the chemical and sensory characteristics of wine. Helpful outcomes for researchers working on sustainability in agriculture. Information will improve the knowledge of wine produced with a highly sustainable management of the vineyard. The results represent crucial outcomes for further investigation. Abstract: The effects of biodynamic production practices on composition and sensory attributes of Sangiovese wines were examined for 2 years (2009 and 2010) in a vineyard that was converted from organic (ORG) to biodynamic (BDN) viticulture. During the first year (2009), the BDN wines were characterised by low alcohol strength, colour intensity, total polyphenols, monomeric anthocyanins and catechin. Conversely, the second year BDN wines differed from the organic wines in terms of total polyphenols and phenolic compounds, including polymeric pigments, co-pigmentation, tannins and iron-reactive polyphenols. The effect of management practices, harvest and their interaction was analysed for each compound. Positive interaction was observed for total acidity, volatile acidity, cyanidin-3-glucoside, protocatechuic acid, (+)-catechin, quercetin and trans -resveratrol. ORG wine initially showed a more complex aroma profile; however, the differences were almost indistinguishable during the second year. Trained panellists highlighted differences in colour intensity between ORG and BDN wines although no preference was found by consumers. The concentrations of ochratoxin A and biogenic amines were far below the health-hazardous threshold.